Learning Foreign Languages at University Level in the Context of Constructivist Paradigm - Burkšaitienė, Nijolė (Acta Paedagogica Vilnensia, 2006)
The article presents an investigation of /earning foreign languages at tertiary level from the constructivist perspective and reports the findings of the research carried out at five universities in Lithuania. The sample of the research included 972 first-year students from 25 major studies; the investigation was aimed at examining (1) the methods of learning English as a foreign language that students are aware of; (2) the status quo of students’ metacognition; (3) relations of variables with the assessment environment that students are familiar with at the initial stage of university studies. The data were analysed using statistical methods of descriptive statistics, distribution frequencies and correlation statistics.